Distinct Genomic Patterns in Pigmented Epithelioid Melanocytoma: A Molecular and Histologic Analysis of 16 Cases. (April 2019) - Isales, Maria C.; Mohan, Lauren S.; Quan, Victor L.; Garfield, Erin M.; Zhang, Bin; Shi, Katherine; Arva, Nicoleta; Beaubier, Nike; Yazdan, Pedram; White, Kevin; Taxter, Timothy J.; Gerami, Pedram
Abstract : Pigmented epithelioid melanocytoma (PEM) is considered an intermediate grade melanocytic lesion that is histologically indistinguishable from epithelioid blue nevi associated with Carney complex. PEM are characterized by an intradermal population of heavily pigmented epithelioid-shaped melanocytes along with some spindled and dendritic melanocytes with frequent melanophages. These melanocytic tumors occasionally involve regional lymph nodes but only rarely result in distant metastases. Recent studies have demonstrated a variable but limited number of specific genomic aberrations including protein kinase A regulatory subunit alpha ( PRKAR1A ), BRAF, GNAQ, and MAP2K1 mutations as well as protein kinase C alpha isoform ( PRKCA ) fusions. We performed an 8-year retrospective review of our database and identified 16 cases of PEM. Using targeted DNA sequencing and RNA-seq to assess 1714 cancer-related genes, we detected gene fusions involving PRKCA in 31% of cases (5/16) with 5' partners SCARB1 (12q24) in 2 cases, CD63 (12q13) in 1 case, ATP2B4 (1q32) in 1 case, and MAP3K3 (17q23) in 1 case. Additional fusions were identified in TPR - NTRK1 (1/16), ALK (1/16), and MYO5A - NTRK3 (1/16). PRKCA fusion lesions tended to occur in younger-aged patients and histologic examination demonstrated sheets of monomorphic epithelioid-shaped melanocytes, moderate to high-grade nuclear atypia, and higher mitotic activity ( P =0.037). Our gene panel also identified previously described mutations in PRKAR1A, GNAQ, MAP2K1, BRAF, NF1 . To our knowledge, this is the largest and most comprehensive study of PEM integrating molecular data with histologic features that can be utilized in future studies for improved subclassification and prognostication of heavily pigmented melanocytic neoplasms.